Analisis Kontribusi Wakaf antara Indonesia dan Malaysia dalam Meningkatkan Pemberdayaan Ekonomi Ummat - Rizki Wahyudi; Yenni Samri Juliati Nasution; Wahyu Syarvina (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Wahyu Syarvina Universitas Islam Negeri Sumatera Utara , wahyusyarvina@uinsu.ac.id3 ABSTRACT. Waqf is one of the Islamic financial instruments that can be empowered to help the ummah's economy, starting to become one of the drivers of helping the economy in the country. because it is not an obligation for a Muslim like zakat, giving rise to various efforts made to collect and distribute waqf so that it can contribute properly. Indonesia and Malaysia, which are two neighboring countries, are the case studies in this study. To see a comparison of the funds raised, a comparative study is a method for analyzing comparisons between the two countries. By collecting data through the library, online sources of scientific publications through the Dompet Dhuafa website and the Malaysian Waqf Foundation, it is also followed by previous studies. It was found that the results of the funds collected were increasing, and the productive empowerment of waqf really helped the community. Keywords: waqf; empowerment; ummah; indonesia; malaysia